Cossack Brigade. Founding, Expansion, Activity in Iran - Kazem Al-Hashimi, Rahim; sahib Idan Al-Badrawi, Hadi (Journal of College of Education, 2022)
The Most historians consider the Cossack Brigade, which was founded in 1879, to be the first modern military formation in Iran. On three paragraphs, which are the beginnings of its establishment, leaders, and expansion, as well as its political and military role in Iran. To obtain our information, we relied on a number of Persian sources, travel books, as well as other foreign sources, and may God grant us success.